2012
DOI: 10.3109/13693786.2011.594967
|View full text |Cite
|
Sign up to set email alerts
|

Long-term surveillance and treatment of subclinical cryptococcosis and nasal colonization byCryptococcus neoformansandC. gattiispecies complex in captive koalas (Phascolarctes cinereus)

Abstract: Cryptococcosis is an important systemic mycosis caused by members of the Cryptococcus neoformans species complex. This disease is potentially fatal in various animals, including koalas. We describe the long-term surveillance and treatment of subclinical cryptococcosis and nasal colonization of koalas by Cryptococcus neoformans and C. gattii. Of the 15 animals investigated through the use of samples obtained by nasal swabs, antigen titer measurements, and pathologic examination, C. neoformans was found associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Six percent of the isolates were recovered from the environment or from animals in Turkey, Israel, Iran, India, Nepal, China, Thailand, Malaysia, Taiwan, Republic of Korea, and Japan (Figure 3). In most of the environmental surveys, C. gattii was isolated from tree samples, namely, from Syzygium cumini , Mimusops elengi , Azadirachta indica , Acacia nilotica , Cassia fistola , Manikara hexandra , Polyalthia longifolia , Eucalyptus camaldulensis , Tamarindus indica , Cassia marginata , and Mangifera indica [32, 33, 177], while the only ten isolates from an animal source were recovered from koalas living in two different zoos in Japan [178, 179]. On the contrary, C. neoformans was prevalently isolated from pigeon and other birds excreta [180] and less frequently from trees such as Eucalyptus tree, Tamarindus arjuna , Tamarindus indica , Cassia fistola , Syzygium cumini , and Ficus religiosa [33, 177, 181, 182], as well as from some vegetables and fruit (tomato, carrot, banana, eggplant, papaya, apple, and guava) [183, 184].…”
Section: Combined Epidemiological Analysismentioning
confidence: 99%
“…Six percent of the isolates were recovered from the environment or from animals in Turkey, Israel, Iran, India, Nepal, China, Thailand, Malaysia, Taiwan, Republic of Korea, and Japan (Figure 3). In most of the environmental surveys, C. gattii was isolated from tree samples, namely, from Syzygium cumini , Mimusops elengi , Azadirachta indica , Acacia nilotica , Cassia fistola , Manikara hexandra , Polyalthia longifolia , Eucalyptus camaldulensis , Tamarindus indica , Cassia marginata , and Mangifera indica [32, 33, 177], while the only ten isolates from an animal source were recovered from koalas living in two different zoos in Japan [178, 179]. On the contrary, C. neoformans was prevalently isolated from pigeon and other birds excreta [180] and less frequently from trees such as Eucalyptus tree, Tamarindus arjuna , Tamarindus indica , Cassia fistola , Syzygium cumini , and Ficus religiosa [33, 177, 181, 182], as well as from some vegetables and fruit (tomato, carrot, banana, eggplant, papaya, apple, and guava) [183, 184].…”
Section: Combined Epidemiological Analysismentioning
confidence: 99%
“…Koalas are susceptible to invasive infection and may act as reservoir hosts for humans by amplifying the environmental burden of C. gattii (187,189). Of interest, in a recent Japanese study of 15 imported Australian koalas in a zoo in Yokohama, only 1 of 10 (66.7%) animals colonized with Cryptococcus was colonized with C. gattii (190). Koalas with invasive cryptococcosis most often present with pneumonia and meningoencephalitis, although nasal infection also occurs (187).…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
“…Koalas with invasive cryptococcosis most often present with pneumonia and meningoencephalitis, although nasal infection also occurs (187). Identification of C. gattii in asymptomatic koalas (188)(189)(190) has spawned studies of subclinical cryptococcosis, of the mechanisms that trigger clinical infection, and of the need for effective cryptococcal eradication measures to prevent the spread of infection.…”
Section: Gattii Infection In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that 10 mg/kg, twice daily, p.o. as monotherapy, was inadequate for effective therapy (Kido et al., ). Thus, on the basis of clinical observations and in vivo studies (Black, Krockenberger, et al., ; Govendir et al., ), this group now recommends administration of oral FLC at 20–25 mg/kg, twice daily, p.o.…”
Section: Anti‐infectivesmentioning
confidence: 99%